Guiding opioid-free intravenous antinociception with the Analgesia Nociception Index: a case report - Coeckelenbergh,Sean (2020)
Abstract Background: Opioid-free anesthesia decreases the incidence of opioid adverse events, but its optimal antinociceptive depth has not been clearly defined. Personalizing intraoperative opioid-free infusions with a nociception monitor may be the solution. Case report: We describe the feasibility and potential limitations of titrating opioid-free antinociception during major abdominal surgery using the Analgesia Nociception Index (Mdoloris, Lille, France) in an obese patient. After stabilizing the patient’s nociception-antinociception balance intraoperatively we quickly reversed anesthesia and the patient did not require postoperative opioids. Conclusion: Personalizing opioid-free antinociception with a nociception monitor is feasible. It may optimize intraoperative antinociception and improve postoperative comfort.